2021
DOI: 10.17582/journal.pjz/20200913170904
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Figures on Covid-19 Pandemic Outbreak

Abstract: Contribution AAA conceived and designed the study. TA executed the experiment. AR and MM analyzed the sera and tissue samples. AR interpreted the data, revised and approved the final version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, upon observing the binding modes of ACE2-SARS-CoV-2 S-protein in human and snake, three regions of snake ACE2 with large structural differences were observed. Within these regions, one compact yet complicated polar interaction network was formed between hACE2 and the S-protein of SARS-CoV-2, yet these polar contacts were not present in snake ACE2, which is the main reason for the reduced ability of snake ACE2 to bind SARS-CoV-2 [98][99][100][101][102]. Further to this, Luan et al [91] have generated structural simulations showing several key contacts of hACE2 with SARS-CoV-2 RBD and found that in snake ACE2, these contacts were completely eradicated.…”
Section: Snakementioning
confidence: 99%
“…Additionally, upon observing the binding modes of ACE2-SARS-CoV-2 S-protein in human and snake, three regions of snake ACE2 with large structural differences were observed. Within these regions, one compact yet complicated polar interaction network was formed between hACE2 and the S-protein of SARS-CoV-2, yet these polar contacts were not present in snake ACE2, which is the main reason for the reduced ability of snake ACE2 to bind SARS-CoV-2 [98][99][100][101][102]. Further to this, Luan et al [91] have generated structural simulations showing several key contacts of hACE2 with SARS-CoV-2 RBD and found that in snake ACE2, these contacts were completely eradicated.…”
Section: Snakementioning
confidence: 99%
“…Covid-19 Epidemiology: On December 31, 2019, the World Health Organization (WHO) was notified of a cluster of unidentified pneumonia cases in Wuhan City, Hubei Province, China. In the first cluster of samples, a new coronavirus was discovered and this novel virus then spread from China to twenty other countries by the end of 2019, with incidents reported on all continents except Antarctica (Muneer et al, 2021;Zahid and Perna, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…WHO established Greek-letter nomenclature for variants and classified them into three groups: variants under monitoring, variants of interest (VOI) and, most importantly, variants of concern (VoC), which demonstrated increased transmissibility and pathogenicity or decreased countermeasures efficiency (WHO, 2022b). The emergence of novel variants raised concerns about vaccines efficacy, which were later confirmed by a number of variants demonstrating different degrees of immune evasion ( Altmann et al, 2021 , Jangra et al, 2021 , Munir et al, 2021 , Singh et al, 2021 , Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%